Individual animal condition connects forest structure with tick infestation and pathogen presence - Diederik Strubbe; Cesare Pacioni; Lander Baeten; Bram Catfolis; Leni Lammens; An Martel; Frank Pasmans; Hein Sprong; Tosca Vanroy; Kris Verheyen; Luc Lens (Biodiversity and Conservation, 2026)
Forest structural complexity is widely assumed to enhance biodiversity, yet its effects on the physiological condition and health of individual organisms remain poorly understood. We examined how forest structural complexity relates to individual condition and, in turn, to ectoparasite and pathogen occurrence in free-living vertebrates. Across 19 temperate forest plots in Flanders (northern Belgium), spanning a gradient of structural complexity, we sampled birds and small mammals and quantified individual condition using scaled mass index, fluctuating asymmetry, and relative telomere length. Larval ticks were collected from hosts and screened for a broad panel of tick-borne pathogens. Relative telomere length tended to be lower in more structurally complex forests, whereas body condition and fluctuating asymmetry showed no consistent relationship with forest structure. Individuals in better body condition were less likely to carry larval ticks. In contrast, hosts with shorter telomeres were more likely to carry pathogen-infected larvae, consistent with links between cumulative physiological stress and infection susceptibility. No evidence was found for systematic co-occurrence among pathogens within larval ticks. Together, our results indicate that individuals interact with forest structure through multiple, potentially independent physiological pathways, shaping observed patterns of parasite load and tick-borne pathogen prevalence.

Heterophil-to-lymphocyte ratio varies with habitat fragmentation and canopy cover in a tropical understory insectivore - Vincent Otieno Onyango; Magdalena Ginko; George Gatere Ndiritu; Laurence Cousseau; Janne Heiskanen; Gladys Nyakeru Kung′u; Peter Njoroge; Mwangi Githiru; Petri Pellikka; Luc Lens; Beate Apfelbeck (Journal of Ornithology, 2026)
Habitat fragmentation and degradation are major problems in tropical forests, leading to a decline in biodiversity. However, it is often unclear which aspects of habitat change are responsible for the decline of specific species. Physiological studies can help identify potential stressors and elucidate causal relationships between habitat change and species decline. In this study, we measured the heterophil-to-lymphocyte (H:L) ratio as an indicator of long-term physiological stress and ecological pressures, such as pathogen exposure or risk of injury, in the tropical understorey insectivore Cabanis’s Greenbul (Placid) ( Phyllastrephus cabanisi placidus ). We then related this ratio to fragment size and forest degradation (canopy cover and vertical vegetation structure). Greenbuls breeding in forest areas with low canopy cover tend to have higher H:L ratios than those breeding in areas with high canopy cover, indicating that low canopy cover creates challenging conditions for greenbuls during breeding. Unexpectedly, however, greenbuls had higher H:L ratios in the largest, most intact forest fragment. These higher H:L ratios in larger fragments may reflect physiological and immunological adjustments to higher ecological pressures, such as predation, parasite prevalence, and competition for territories, due to intact trophic networks. This study therefore advocates concerted efforts to preserve large forest fragments, while smaller fragments should be rehabilitated to strengthen the ecological corridors and networks of these key biodiversity areas, which are of high conservation priority within the isolated mountain peaks of the Taita Hills in Kenya.

Forest Degradation and Weather Jointly Affect Early‐Life Development in a Tropical Understory Bird - Gladys Nyakeru Kung'u; Laurence Cousseau; Virginie Canoine; Janne Heiskanen; Mwangi Githiru; Peter Njoroge; Petri Pellikka; Jan Christian Habel; Luc Lens; Beate Apfelbeck (Global Change Biology, 2026)
Tropical forest birds face mounting pressures from habitat loss, degradation, and climate warming, yet their combined effects on early‐life development remain unclear. Using over a decade of morphological and behavioural observations from Kenya's Taita Hills and 4 years of nestling corticosterone measurements across eight forest patches differing in size and degradation, we examined how forest quality and climate shape nestling condition in the understorey insectivore placid greenbul ( Phyllastrephus cabanisi placidus ). Nestlings in smaller or more degraded patches showed lower body condition. Provisioning rates did not vary with forest quality, suggesting that poor condition in degraded habitats may result from lower prey quality rather than reduced parental effort. Unexpectedly, corticosterone levels were higher in larger forest patches, and nestlings with elevated corticosterone also showed more advanced wing development, indicating that corticosterone here may reflect developmental stage (readiness to fledge) rather than condition per se. In addition, nestling condition declined in hot weather. Furthermore, although body extremities were shorter in small or degraded patches at low temperatures, in hot weather nestlings developed extremities similar in length to those in larger, less degraded forest patches, consistent with short‐term thermoregulatory plasticity. By contrast, in high‐canopy areas tarsus growth decreased with increasing temperature, highlighting that multiple developmental mechanisms may operate simultaneously. High canopy cover also buffered body condition under dry weather, whereas nestlings in low‐canopy habitats were particularly vulnerable during drought. Our findings demonstrate how forest degradation and climate interact to shape nestling growth, physiology, and potential thermal plasticity. Maintaining intact forest canopies and large forest patches is thus critical for preserving the microclimatic buffering needed to support offspring development in a warming climate. Because multiple, and sometimes opposing, developmental mechanisms may act simultaneously, integrating morphological, behavioural, and physiological indicators provides a powerful multi‐metric approach to disentangle how habitat and climate jointly shape early‐life development.

Early-life social instability affects aggression, but not response inhibition, in chickens - Kathryn Willcox; Alizée Vernouillet; Birgit Szabo; An Martel; Luc Lens; Frederick Verbruggen (acta ethologica, 2026)

Habitat degradation relates to reduced immune function in nestlings, but not adults, of a tropical forest bird - Tamara Isabelle Sorg; Arne Hegemann; Laurence Cousseau; Gladys Nyakeru Kung’u; Janne Heiskanen; Petri Pellikka; Mwangi Githiru; Luc Lens; Beate Apfelbeck (The Science of Nature, 2025)
Human-induced habitat loss, fragmentation and degradation are among the leading causes of species decline worldwide. This is particularly true in tropical forests, where unique, often highly specialized fauna is under threat. By altering resource availability, anthropogenic habitat change can impose resource constraints on animals and may influence their allocation of resources to competing life history traits. In this study, we investigated whether nestlings and adults differently invest in self-maintenance depending on habitat degradation in the placid greenbul ( Phyllastrephus cabanisi placidus ), a cooperative breeder native to the cloud forests of Eastern Africa. We quantified investment in self-maintenance by measuring innate immune function using bacteria killing assays (BKAs) in adult breeders and their nestlings along a gradient of fragmented and degraded forests of the Kenyan Taita Hills. While innate immune function is an important defence against pathogens, resources needed to maintain it may come at a cost to other processes such as nestling development. We show that while forest degradation did not affect adult innate immune function, nestlings bear the cost of growing up in degraded habitats, as their ability to clear bacteria from blood plasma was lower in areas with degraded vegetation. These findings highlight the importance of studying the effects of habitat fragmentation and degradation in the tropics, where most of the global biodiversity occurs, and where long-lived species may respond differently from short-lived temperate ones, for example by prioritising self-preservation over reproduction.

Spatiotemporal differences in plastic biovectoring among three sympatric waterbirds - Julián Cano-Povedano; Cosme López-Calderón; Francisco Hortas; Victor Martín-Vélez; Marta I. Sánchez; Belén Cañuelo-Jurado; Andrés Cózar; Judy Shamoun-Baranes; Wendt Müller; Chris B. Thaxter; Luc Lens; Eric Stienen; et al. (Environmental Research, 2025)

Habitat disturbance alters movement behaviour in a social Afrotropical forest bird - Gladys Nyakeru Kung'u; Christina Fischer; Janne Heiskanen; Laurence Cousseau; Mwangi Githiru; Jan Christian Habel; Kim G. Mortega; Peter Njoroge; Linda Alila; Petri Pellikka; Luc Lens; Beate Apfelbeck (Biological Conservation, 2025)

Partial migration pays off in black-faced cormorants: insights from post-breeding GPS tracking - Thomas Cansse; Luc Lens; Rachael A. Orben; Grace J. Sutton; Jonathan A. Botha; John P.Y. Arnould (Marine Biology, 2024)
Seasonal variation in food availability or adverse weather patterns can create challenging conditions for year-round survival. Birds experiencing such fluctuations may migrate to locations with better food availability in the non-breeding period. While some species are obligate migrants, others are facultative migrants where various post-breeding strategies exist within populations. Several cormorant and shag species are facultative migrants with a range of post-breeding movement strategies within populations. Currently, most of the information available on cormorant post-breeding strategies originates from banding studies and little is known about their movements, time budget or habitat use during the non-breeding period. In the present study, Australian endemic black-faced cormorants ( Phalacrocorax fuscescens ), breeding on Notch Island, Victoria, were tracked with GPS data loggers during the non-breeding period. Different post-breeding strategies were observed. Individuals were either resident ( N = 36, 69%), remaining within a short distance of the colony (16.7 ± 2.2 km) or migratory ( N = 16, 31%), travelling greater distances (250.7 ± 24.4 km) to establish a new central place foraging location. Data from individuals which covered the entire non-breeding period indicated that, across strategies, individual birds had one area of residency during the non-breeding period. Migratory individuals were found to have lower daily activity levels, spending less time flying and foraging, than resident individuals during the early non-breeding period, possibly indicating that they had access to greater prey resources. Regardless of the post-breeding strategy, individuals utilised foraging locations that were of similar seabed depths year-round suggesting individual specialisation in prey resources or foraging habitats.

The effect of forest structural complexity on tick-borne pathogens in questing ticks and small mammals - Tosca Vanroy; An Martel; Lander Baeten; Manoj Fonville; Luc Lens; Frank Pasmans; Hein Sprong; Diederik Strubbe; Mats Van Gestel; Kris Verheyen (Forest Ecology and Management, 2024)

Great tits (Parus major) in a west European temperate forest show little seasonal variation in metabolic energy requirements - Cesare Pacioni; Marina Sentís; Catherine Hambly; John R. Speakman; Anvar Kerimov; Andrey Bushuev; Luc Lens; Diederik Strubbe (Journal of Thermal Biology, 2023)

Where are we now with European forest multi-taxon biodiversity and where can we head to? - Sabina Burrascano; Francesco Chianucci; Giovanni Trentanovi; Sebastian Kepfer-Rojas; Tommaso Sitzia; Flóra Tinya; Inken Doerfler; Yoan Paillet; Thomas Andrew Nagel; Bozena Mitic; Lourdes Morillas; Silvana Munzi; et al. (Biological Conservation, 2023)

Anthropogenic activities affect forest structure and arthropod abundance in a Kenyan biodiversity hotspot - Gladys Nyakeru Kung’u; Laurence Cousseau; Mwangi Githiru; Jan Christian Habel; Mwangi Kinyanjui; Kennedy Matheka; Christine B. Schmitt; Tobias Seifert; Mike Teucher; Luc Lens; Beate Apfelbeck (Biodiversity and Conservation, 2023)
Land-use change remains the main threat to tropical forests and their dependent fauna and flora, and degradation of existing forest remnants will further accelerate species loss. Forest degradation may result directly from human forest use or through spatial effects of land-use change. Understanding the drivers of forest degradation and its effects on biodiversity is pivotal for formulating impactful forest management and monitoring protocols, but such knowledge is lacking for many biodiversity hotspots, such as the Taita Hills in southeast Kenya. Here we first quantify effects of social factors (human activity and presence) at plot and landscape level, forest management (gazetted vs. non-gazetted) and spatial factors (fragment size and distance to forest edge) on the vegetation structure of indigenous Taita forest fragments. Next, we quantify effects of degraded vegetation structure on arthropod abundance and diversity. We show that human presence and activity at both the plot and landscape level explain variation in vegetation structure. We particularly provide evidence that despite a national ban on cutting of indigenous trees, poaching of pole-sized trees for subsistence use may be simplifying vegetation structure, with the strongest effects in edge-dominated, small forest fragments. Furthermore, we found support for a positive effect of vegetation structure on arthropod abundance, although the effect of daily maximum temperature and yearly variation was more pronounced. Maintenance of multi-layered forest vegetation in addition to reforestation maybe a key to conservation of the endangered and endemic fauna of the Taita Hills.

Contrasting effects of cooperative group size and number of helpers on maternal investment in eggs and nestlings - Dries Van de Loock; Laurence Cousseau; Beate Apfelbeck; Mwangi Githiru; Luc Lens; Erik Matthysen (Animal Behaviour, 2023)

Seasonal variation in thermoregulatory capacity of three closely related Afrotropical Estrildid finches introduced to Europe - Cesare Pacioni; Marina Sentís; Anvar Kerimov; Andrey Bushuev; Luc Lens; Diederik Strubbe (Journal of Thermal Biology, 2023)

Widespread triazole pesticide use affects infection dynamics of a global amphibian pathogen - Andrea Barbi; Tess Goessens; Diederik Strubbe; Arne Deknock; Robby Van Leeuwenberg; Niels De Troyer; Elin Verbrugghe; Mark Greener; Siegrid De Baere; Luc Lens; Peter Goethals; An Martel; et al. (Ecology Letters, 2023)
The sixth mass extinction is a consequence of complex interplay between multiple stressors with negative impact on biodiversity. We here examine the interaction between two globally widespread anthropogenic drivers of amphibian declines: the fungal disease chytridiomycosis and antifungal use in agriculture. Field monitoring of 26 amphibian ponds in an agricultural landscape shows widespread occurrence of triazole fungicides in the water column throughout the amphibian breeding season, together with a negative correlation between early season application of epoxiconazole and the prevalence of chytrid infections in aquatic newts. While triazole concentrations in the ponds remained below those that inhibit growth of Batrachochytrium dendrobatidis , they bioaccumulated in the newts' skin up to tenfold, resulting in cutaneous growth‐suppressing concentrations. As such, a concentration of epoxiconazole, 10 times below that needed to inhibit fungal growth, prevented chytrid infection in anuran tadpoles. The widespread presence of triazoles may thus alter chytrid dynamics in agricultural landscapes.

Territoriality constrains foraging activity and has carry-over effects on reproductive investment - Reyes Salas; Jan Baert; Eric Stienen; Luc Lens; Wendt Müller (Marine Biology, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Niche evolution reveals disparate signatures of speciation in the ‘great speciator’ (white‐eyes, Aves: Zosterops ) - Jan O. Engler; Yvonne Lawrie; Juliano S. Cabral; Luc Lens; Enrique Martínez‐Meyer (Journal of Biogeography, 2021)
Aim Recent breakthroughs in environmental niche models (ENMs) have substantially improved our insights in niche evolution. Assuming that closely related taxa have similar niches (i.e. niche conservatism), the combination of ENMs with phylogenetic information allows the reconstruction of ancestral niches. This reconstruction helps to identify the underlying speciation processes leading to diversification (i.e. ecological speciation under niche divergence and mutation‐order speciation under niche conservatism). Here, we studied the niche evolution in white‐eyes (the so‐called ‘great speciator’) to understand their extraordinarily fast diversification rate, wide distribution and rather conserved phenotypes. In a broader perspective, unravelling niche evolution in white‐eyes can shed light on how different niche properties such as climate, habitat or trophic level may contribute to diversification. Location Asian‐Pacific and Afrotropics. Taxon White‐eyes (Aves, genus: Zosterops ). Methods We selected 10 wide‐ranging taxa that are equally distributed across the genus’ range and phylogeny. We studied niche evolution for a series of thermal and precipitation‐related niche axes separately. We used a time‐calibrated phylogeny encompassing the study taxa and estimated ancestral environmental niches in geographic and environmental niche spaces. Results We found that niche evolution in Zosterops is primarily driven by ecological speciation. Thermal niches, in particular, are characterized by a higher level of conservatism, as compared to precipitation‐related niche axes. The fact that the youngest species diverged strongest stands in stark contrast to expectations stemming from niche conservatism. Main conclusions Contrasting evolutionary patterns in different niche axes suggest different underlying evolutionary pressures. Hence, future studies on niche evolution should take possible disparities between niche axes into account.

Exploring the faecal microbiome of the Eurasian nuthatch (Sitta europaea) - Evy Goossens; Roschong Boonyarittichaikij; Daan Dekeukeleire; Sarah Van Praet; Dries Bonte; Kris Verheyen; Luc Lens; An Martel; Elin Verbrugghe (Archives of Microbiology, 2021)

Microclimate limits thermal behaviour favourable to disease control in a nocturnal amphibian - Wouter Beukema; Frank Pasmans; Sarah Van Praet; Francisco Ferri‐Yáñez; Moira Kelly; Alexandra E. Laking; Jesse Erens; Jeroen Speybroeck; Kris Verheyen; Luc Lens; An Martel (Ecology Letters, 2021)
While epizootics increasingly affect wildlife, it remains poorly understood how the environment shapes most host–pathogen systems. Here, we employ a three‐step framework to study microclimate influence on ectotherm host thermal behaviour, focusing on amphibian chytridiomycosis in fire salamanders ( Salamandra salamandra ) infected with the fungal pathogen Batrachochytrium salamandrivorans ( Bsal ). Laboratory trials reveal that innate variation in thermal preference, rather than behavioural fever, can inhibit infection and facilitate salamander recovery under humidity‐saturated conditions. Yet, a 3‐year field study and a mesocosm experiment close to the invasive Bsal range show that microclimate constraints suppress host thermal behaviour favourable to disease control. A final mechanistic model, that estimates range‐wide, year‐round host body temperature relative to microclimate, suggests that these constraints are rule rather than exception. Our results demonstrate how innate host defences against epizootics may remain constrained in the wild, which predisposes to range‐wide disease outbreaks and population declines.

Early colonization stages of fabric carriers by two Chlorella strains - Jairo Hernán Moreno Osorio; Antonino De Natale; Angelo Del Mondo; Luigi Frunzo; Piet Nicolaas Luc Lens; Giovanni Esposito; Antonino Pollio (Journal of Applied Phycology, 2020)

Support for the habitat amount hypothesis from a global synthesis of species density studies - James I. Watling; Victor Arroyo‐Rodríguez; Marion Pfeifer; Lander Baeten; Cristina Banks‐Leite; Laura M. Cisneros; Rebecca Fang; A. Caroli Hamel‐Leigue; Thibault Lachat; Inara R. Leal; Luc Lens; Hugh P. Possingham; et al. (Ecology Letters, 2020)
Decades of research suggest that species richness depends on spatial characteristics of habitat patches, especially their size and isolation. In contrast, the habitat amount hypothesis predicts that (1) species richness in plots of fixed size (species density) is more strongly and positively related to the amount of habitat around the plot than to patch size or isolation; (2) habitat amount better predicts species density than patch size and isolation combined, (3) there is no effect of habitat fragmentation per se on species density and (4) patch size and isolation effects do not become stronger with declining habitat amount. Data on eight taxonomic groups from 35 studies around the world support these predictions. Conserving species density requires minimising habitat loss, irrespective of the configuration of the patches in which that habitat is contained.

Urbanization drives cross‐taxon declines in abundance and diversity at multiple spatial scales - Elena Piano; Caroline Souffreau; Thomas Merckx; Lisa F. Baardsen; Thierry Backeljau; Dries Bonte; Kristien I. Brans; Marie Cours; Maxime Dahirel; Nicolas Debortoli; Ellen Decaestecker; Katrien De Wolf; et al. (Global Change Biology, 2020)
The increasing urbanization process is hypothesized to drastically alter (semi‐)natural environments with a concomitant major decline in species abundance and diversity. Yet, studies on this effect of urbanization, and the spatial scale at which it acts, are at present inconclusive due to the large heterogeneity in taxonomic groups and spatial scales at which this relationship has been investigated among studies. Comprehensive studies analysing this relationship across multiple animal groups and at multiple spatial scales are rare, hampering the assessment of how biodiversity generally responds to urbanization. We studied aquatic (cladocerans), limno‐terrestrial (bdelloid rotifers) and terrestrial (butterflies, ground beetles, ground‐ and web spiders, macro‐moths, orthopterans and snails) invertebrate groups using a hierarchical spatial design, wherein three local‐scale (200 m × 200 m) urbanization levels were repeatedly sampled across three landscape‐scale (3 km × 3 km) urbanization levels. We tested for local and landscape urbanization effects on abundance and species richness of each group, whereby total richness was partitioned into the average richness of local communities and the richness due to variation among local communities. Abundances of the terrestrial active dispersers declined in response to local urbanization, with reductions up to 85% for butterflies, while passive dispersers did not show any clear trend. Species richness also declined with increasing levels of urbanization, but responses were highly heterogeneous among the different groups with respect to the richness component and the spatial scale at which urbanization impacts richness. Depending on the group, species richness declined due to biotic homogenization and/or local species loss. This resulted in an overall decrease in total richness across groups in urban areas. These results provide strong support to the general negative impact of urbanization on abundance and species richness within habitat patches and highlight the importance of considering multiple spatial scales and taxa to assess the impacts of urbanization on biodiversity.

Forest fragmentation modulates effects of tree species richness and composition on ecosystem multifunctionality - Lionel R. Hertzog; Roschong Boonyarittichaikij; Daan Dekeukeleire; Stefanie R. E. de Groote; Irene M. van Schrojenstein Lantman; Bram K. Sercu; Hannah Keely Smith; Eduardo de la Peña; Martijn L. Vandegehuchte; Dries Bonte; An Martel; Kris Verheyen; et al. (Ecology, 2019)
Forest fragments in highly disturbed landscapes provide important ecosystem services ranging from acting as biodiversity reservoir to providing timber or regulating hydrology. Managing the tree species richness and composition of these fragments to optimize their functioning and the deliverance of multiple ecosystem services is of great practical relevance. However, both the strength and direction of tree species richness and tree species composition effects on forest ecosystem multifunctionality may depend on the landscape context in which these forest remnants are embedded. Taking advantage of an observatory network of 53 temperate forest plots varying in tree species richness, tree species composition, and fragmentation intensity we measured 24 ecosystem functions spanning multiple trophic levels and analyzed how tree species diversity–multifunctionality relationships changed with fragmentation intensity. Our results show that fragmentation generally increases multifunctionality and strengthens its positive relationship with diversity, possibly due to edge effects. In addition, different tree species combinations optimize functioning under different fragmentation levels. We conclude that management and restoration of forest fragments aimed at maximizing ecosystem multifunctionality should be tailored to the specific landscape context. As forest fragmentation will continue, tree diversity will become increasingly important to maintain forest functioning.

Tree species diversity indirectly affects nutrient cycling through the shrub layer and its high-quality litter - Stefanie R. E. De Groote; Margot Vanhellemont; Lander Baeten; An De Schrijver; An Martel; Dries Bonte; Luc Lens; Kris Verheyen (Plant and Soil, 2018)

GPS tracking during parental care does not affect early offspring development in lesser black-backed gulls - Marwa M. Kavelaars; Eric Stienen; Hans Matheve; Roland-Jan Buijs; Luc Lens; Wendt Müller (Marine Biology, 2018)

Using abundance and habitat variables to identify high conservation value areas for threatened mammals - Luc Roscelin Dongmo Tédonzong; Jacob Willie; Ada Myriane Patipe Keuko; Jacques Keumo Kuenbou; Giscard Njotah; Martin N. Tchamba; Nikki Tagg; Luc Lens (Biodiversity and Conservation, 2018)

East African coastal forest under pressure - Jan Christian Habel; Ivon Constanza Cuadros Casanova; Camilo Zamora; Mike Teucher; Berthold Hornetz; Halimu Shauri; Ronald K. Mulwa; Luc Lens (Biodiversity and Conservation, 2017)

Urbanization drives community shifts towards thermophilic and dispersive species at local and landscape scales - Elena Piano; Katrien De Wolf; Francesca Bona; Dries Bonte; Diana E. Bowler; Marco Isaia; Luc Lens; Thomas Merckx; Daan Mertens; Marc van Kerckvoorde; Luc De Meester; Frederik Hendrickx (Global Change Biology, 2017)
The increasing conversion of agricultural and natural areas to human‐dominated urban landscapes is predicted to lead to a major decline in biodiversity worldwide. Two conditions that typically differ between urban environments and the surrounding landscape are increased temperature, and high patch isolation and habitat turnover rates. However, the extent and spatial scale at which these altered conditions shape biotic communities through selection and/or filtering on species traits are currently poorly understood. We sampled carabid beetles at 81 sites in Belgium using a hierarchically nested sampling design wherein three local‐scale (200 × 200 m) urbanization levels were repeatedly sampled across three landscape‐scale (3 × 3 km) urbanization levels. First, we showed that communities sampled in the most urbanized locations and landscapes displayed a distinct species composition at both local and landscape scale. Second, we related community means of species‐specific thermal preferences and dispersal capacity (based on European distribution and wing morphology, respectively) to the urbanization gradients. We showed that urban communities consisted on average of species with a preference for higher temperatures and with better dispersal capacities compared to rural communities. These shifts were caused by an increased number of species tolerating higher temperatures, a decreased richness of species with low thermal preference, and an almost complete depletion of species with very low‐dispersal capacity in the most urbanized localities. Effects of urbanization were most clearly detected at the local scale, although more subtle effects could also be found at the scale of entire landscapes. Our results demonstrate that urbanization may fundamentally and consistently alter species composition by exerting a strong filtering effect on species dispersal characteristics and favouring replacement by warm‐dwelling species.

More topics from the tropics: additional thoughts to Mammides et al. - Jan Christian Habel; Luc Lens; Hilde Eggermont; Mwangi Githiru; Ronald K. Mulwa; Halimu Suleiman Shauri; Thomas M. Lewinsohn; Wolfgang W. Weisser; Thomas Schmitt (Biodiversity and Conservation, 2017)

Nature conservation at the edge - Jan Christian Habel; Mike Teucher; Ronald K. Mulwa; Wolfgang Haber; Hilde Eggermont; Luc Lens (Biodiversity and Conservation, 2016)

Real-world complexity of food security and biodiversity conservation - Jan Christian Habel; Mike Teucher; Berthold Hornetz; Ralph Jaetzold; Josphert N. Kimatu; Sichangi Kasili; Zachariah Mairura; Ronald K. Mulwa; Hilde Eggermont; Wolfgang W. Weisser; Luc Lens (Biodiversity and Conservation, 2015)

Towards more equal footing in north–south biodiversity research: European and sub-Saharan viewpoints - Jan Christian Habel; Hilde Eggermont; Sven Günter; Ronald K. Mulwa; Marco Rieckmann; Lian Pin Koh; Saliou Niassy; J. Willem H. Ferguson; Gelaye Gebremichael; Mwangi Githiru; Wolfgang W. Weisser; Luc Lens (Biodiversity and Conservation, 2014)

Lowland panmixia versus highland disjunction: genetic and bioacoustic differentiation in two species of East African White-eye birds - Jan Christian Habel; Werner Ulrich; Gustav Peters; Martin Husemann; Luc Lens (Conservation Genetics, 2014)

Nest predation in Afrotropical forest fragments shaped by inverse edge effects, timing of nest initiation and vegetation structure - Toon Spanhove; Tom Callens; Caspar A. Hallmann; Petri Pellikka; Luc Lens (Journal of Ornithology, 2014)

Plant selection for nest building by western lowland gorillas in Cameroon - Jacob Willie; Nikki Tagg; Charles-Albert Petre; Zjef Pereboom; Luc Lens (Primates, 2014)

Population genetics of the East African White-eye species complex - Jan Christian Habel; Siobhan Cox; Franz Gassert; Ronald K. Mulwa; Jobst Meyer; Luc Lens (Conservation Genetics, 2013)

Intra-clutch variation in avian eggshell pigmentation covaries with female quality - Greet De Coster; Liesbeth De Neve; Luc Lens (Journal of Ornithology, 2013)

Mind the gaps when using science to address conservation concerns - Jan Christian Habel; Martin M. Gossner; Sebastian T. Meyer; Hilde Eggermont; Luc Lens; Jürgen Dengler; Wolfgang W. Weisser (Biodiversity and Conservation, 2013)

The genetic signature of ecologically different grassland Lepidopterans - Jan Christian Habel; Dennis Rödder; Luc Lens; Thomas Schmitt (Biodiversity and Conservation, 2013)

Food security versus biodiversity protection: an example of land-sharing from East Africa - Jan Christian Habel; Wolfgang W. Weisser; Hilde Eggermont; Luc Lens (Biodiversity and Conservation, 2013)

Intraclutch variation in avian eggshell pigmentation: the anaemia hypothesis - Greet De Coster; Liesbeth De Neve; Luc Lens (Oecologia, 2012)

Quantifying population structure on short timescales - JOOST A. M. RAEYMAEKERS; LUC LENS; FREDERIK VAN den BROECK; STEFAN VAN DONGEN; FILIP A. M. VOLCKAERT (Molecular Ecology, 2012)
Quantifying the contribution of the various processes that influence population genetic structure is important, but difficult. One of the reasons is that no single measure appropriately quantifies all aspects of genetic structure. An increasing number of studies is analysing population structure using the statistic D, which measures genetic differentiation, next to G ST , which quantifies the standardized variance in allele frequencies among populations. Few studies have evaluated which statistic is most appropriate in particular situations. In this study, we evaluated which index is more suitable in quantifying postglacial divergence between three‐spined stickleback ( Gasterosteus aculeatus ) populations from Western Europe. Population structure on this short timescale (10 000 generations) is probably shaped by colonization history, followed by migration and drift. Using microsatellite markers and anticipating that D and G ST might have different capacities to reveal these processes, we evaluated population structure at two levels: (i) between lowland and upland populations, aiming to infer historical processes; and (ii) among upland populations, aiming to quantify contemporary processes. In the first case, only D revealed clear clusters of populations, putatively indicative of population ancestry. In the second case, only G ST was indicative for the balance between migration and drift. Simulations of colonization and subsequent divergence in a hierarchical stepping stone model confirmed this discrepancy, which becomes particularly strong for markers with moderate to high mutation rates. We conclude that on short timescales, and across strong clines in population size and connectivity, D is useful to infer colonization history, whereas G ST is sensitive to more recent demographic events.

Effects of early developmental conditions on innate immunity are only evident under favourable adult conditions in zebra finches - Greet De Coster; Simon Verhulst; Egbert Koetsier; Liesbeth De Neve; Michael Briga; Luc Lens (The Science of Nature, 2011)

Genetic signature of population fragmentation varies with mobility in seven bird species of a fragmented Kenyan cloud forest - TOM CALLENS; PETER GALBUSERA; ERIK MATTHYSEN; ERIC Y. DURAND; MWANGI GITHIRU; JEROEN R. HUYGHE; LUC LENS (Molecular Ecology, 2011)
Habitat fragmentation can restrict geneflow, reduce neighbourhood effective population size, and increase genetic drift and inbreeding in small, isolated habitat remnants. The extent to which habitat fragmentation leads to population fragmentation, however, differs among landscapes and taxa. Commonly, researchers use information on the current status of a species to predict population effects of habitat fragmentation. Such methods, however, do not convey information on species‐specific responses to fragmentation. Here, we compare levels of past population differentiation, estimated from microsatellite genotypes, with contemporary dispersal rates, estimated from multi‐strata capture–recapture models, to infer changes in mobility over time in seven sympatric, forest‐dependent bird species of a Kenyan cloud forest archipelago. Overall, populations of sedentary species were more strongly differentiated and clustered compared to those of vagile ones, while geographical patterning suggested an important role of landscape structure in shaping genetic variation. However, five of seven species with broadly similar levels of genetic differentiation nevertheless differed substantially in their current dispersal rates. We conclude that post‐fragmentation levels of vagility, without reference to past population connectivity, may not be the best predictor of how forest fragmentation affects the life history of forest‐dependent species. As effective conservation strategies often hinge on accurate prediction of shifts in ecological and genetic relationships among populations, conservation practices based solely upon current population abundances or movements may, in the long term, prove to be inadequate.

Woody plant communities of isolated Afromontane cloud forests in Taita Hills, Kenya - Raf Aerts; Koen W. Thijs; Valérie Lehouck; Henk Beentje; Benny Bytebier; Erik Matthysen; Hubert Gulinck; Luc Lens; Bart Muys (Plant Ecology, 2011)

Limnological and ecological sensitivity of Rwenzori mountain lakes to climate warming - Hilde Eggermont; Dirk Verschuren; Leen Audenaert; Luc Lens; James Russell; Gerrit Klaassen; Oliver Heiri (Hydrobiologia, 2010)

Pervasive effects of dispersal limitation on within‐ and among‐community species richness in agricultural landscapes - Frederik Hendrickx; Jean‐Pierre Maelfait; Konjev Desender; Stephanie Aviron; Debra Bailey; Tim Diekotter; Luc Lens; Jaan Liira; Oliver Schweiger; Marjan Speelmans; Viki Vandomme; Rob Bugter (Global Ecology and Biogeography, 2009)
Aim To determine whether the effect of habitat fragmentation and habitat heterogeneity on species richness at different spatial scales depends on the dispersal ability of the species assemblages and if this results in nested species assemblages. Location Agricultural landscapes distributed over seven temperate Europe countries covering a range from France to Estonia. Methods We sampled 16 local communities in each of 24 agricultural landscapes (16 km 2 ) that differ in the amount and heterogeneity of semi‐natural habitat patches. Carabid beetles were used as model organisms as dispersal ability can easily be assessed on morphological traits. The proximity and heterogeneity of semi‐natural patches within the landscape were related to average local (alpha), between local (beta) and landscape (gamma) species richness and compared among four guilds that differ in dispersal ability. Results For species assemblages with low dispersal ability, local diversity increased as the proximity of semi‐natural habitat increased, while mobile species showed an opposite trend. Beta diversity decreased equally for all dispersal classes in relation to proximity, suggesting a homogenizing effect of increased patch isolation. In contrast, habitat diversity of the semi‐natural patches affected beta diversity positively only for less mobile species, probably due to the low dispersal ability of specialist species. Species with low mobility that persisted in highly fragmented landscapes were consistently present in less fragmented ones, resulting in nested assemblages for this mobility class only. Main conclusions The incorporation of dispersal ability reveals that only local species assemblages with low dispersal ability show a decrease of richness as a result of fragmentation. This local species loss is compensated at least in part by an increase in species with high dispersal ability, which obscures the effect of fragmentation when investigated across dispersal groups. Conversely, fragmentation homogenizes the landscape fauna for all dispersal groups, which indicates the invasion of non‐crop habitats by similar good dispersers across the whole landscape. Given that recolonization of low dispersers is unlikely, depletion of these species in modern agricultural landscapes appears temporally pervasive.

Land rehabilitation and the conservation of birds in a degraded Afromontane landscape in northern Ethiopia - Raf Aerts; Frederik Lerouge; Eva November; Luc Lens; Martin Hermy; Bart Muys (Biodiversity and Conservation, 2008)

Genetic equilibrium despite habitat fragmentation in an Afrotropical bird - Peter Galbusera; Mwangi Githiru; Luc Lens; Erik Matthysen (Molecular Ecology, 2004)
We examined the effects of habitat fragmentation of the white‐starred robin Pogonocichla stellata metapopulation in the Taita Hills archipelago, a hotspot for biodiversity which was fragmented ~40 years ago. Using seven microsatellite markers, we analysed the robin's genetic structure and tested for equilibrium between migration and drift (testing the probability of decreased dispersal) as well as between mutation and drift (test for recent reduction in effective population size, i.e. bottlenecks). This metapopulation was found to retain relatively high levels of genetic variability ( H E between 0.63 and 0.71) and to be in migration–drift equilibrium, suggesting that increased isolation between fragments did not have much effect on the dispersal between them. Furthermore, this equilibrium test greatly enhanced the interpretation of parameters (e.g. F ST ) assumed to have reached an equilibrium value. In contrast to previous findings on the related and sympatric Taita thrush Turdus helleri (which is critically endangered), there were no indications for recent bottlenecks in any of the robin subpopulations. This difference can be attributed to the higher dispersal capacity of the robin compared with the thrush (deduced from both the genetic and capture–recapture data). Our results stress the importance of sustained dispersal for species conservation.

Patch quality and connectivity influence spatial dynamics in a dune wolfspider - Dries Bonte; Luc Lens; Jean-Pierre Maelfait; Maurice Hoffmann; Eckhart Kuijken (Oecologia, 2003)

Fluctuating asymmetry as a bio‐indicator in isolated populations of the Taita thrush: a Bayesian perspective - Luc Lens; Stefan Van Dongen (Journal of Biogeography, 2002)
Aim We examined whether developmental instability can be used as a bio‐monitoring tool in the endangered Taita thrush ( Turdus helleri L.) through the measurement of individual levels of fluctuating asymmetry in tarsus length. Because estimates of the association between developmental instability, stress and fitness derived from traditional regression are biased, we compared parameter estimates obtained from likelihood based analysis with those obtained from a Bayesian latent variable model. Location Taita thrushes were captured and measured in three isolated cloud forest fragments located in the Taita Hills of south‐east Kenya. Methods We applied mixed‐effects regression with Restricted Maximum Likelihood parameter estimation (performed with SAS version 8.0) and Bayesian latent variable modelling (performed with WINBUGS version 1.3 and CODA version 0.4) to estimate unbiased levels of developmental instability and to model relationships between developmental instability and body condition in 312 Taita thrushes. Results Likelihood and Bayesian analyses yielded highly comparable results. Individual levels of developmental instability were strongly inversely related to body condition in the subpopulation with the lowest average condition. In contrast, both variables were unrelated in two other subpopulations with higher average condition. Such heterogeneity in association was in the direction expected by developmental theory, given that higher condition suggests more benign ambient conditions. The estimated levels of body condition in the three subpopulations did not support their presumed ranking in relation to environmental stress. Developmental instability and body condition are therefore believed to reflect different aspects of individual fitness. Main conclusions Variation in developmental homeostasis, either modelled as observable variable (fluctuating asymmetry) or latent variable (developmental instability), appears a useful indicator of stress effects in the Taita thrush. Because relationships between environmental stress and developmental instability may depend on the extent to which stress‐mediated changes in other components of phenotypic variation are correlated, the study of trait asymmetry should preferably be combined with that of other measures of trait variability, such as trait size or organismal condition.

Fluctuating Asymmetry as an Early Warning System in the Critically Endangered Taita Thrush - Luc Lens; Stefan Van Dongen; Erik Matthysen (Conservation Biology, 2002)
Environmental and genetic factors increasingly stress natural populations, and conservationists need simple tools to measure the effect of these stresses before populations become irreversibly affected. The inability of an organism to withstand random perturbations during its development—so‐called developmental instability—has been proposed as a potential early indicator of stress. To act as a true early warning system, however, stress‐mediated changes in developmental instability should be manifest in the phenotype before major changes occur in more direct components of fitness. We tested this hypothesis by estimating the survival probabilities of 260 Taita Thrushes ( Turdus helleri ) inhabiting three differentially disturbed forest fragments ( little, moderately, and highly deteriorated) and relating these to individual estimates of tarsus asymmetry (a measure of developmental instability), two other putative indices of expected fitness (size and body condition), and a coefficient of inbreeding. Tarsus symmetry, but not survival, was lower in the moderately disturbed population than in the least disturbed one, whereas both symmetry and survival were lower in the most disturbed population. Thus, higher levels of habitat disturbance were reflected by increased population levels of asymmetry before a decrease in survival became apparent. In contrast, none of the other variables showed a significant response to habitat disturbance. At the individual level, asymmetric thrushes showed lower probabilities of survival than more symmetric ones, and the magnitude of the relationship increased with habitat disturbance. Birds in better condition (i.e., higher residual body mass) survived better, irrespective of the quality of the habitat. The key finding that stress‐mediated increase in fluctuating asymmetry may precede decrease in survival suggests that single‐trait asymmetry can serve as an early warning system in conservation.

Genetic variability and gene flow in the globally, critically-endangered Taita thrush - Peter Galbusera; Luc Lens; Tine Schenck; Edward Waiyaki; Erik Matthysen (Conservation Genetics, 2000)

Nest-building by crested tit Parus cristatus males: an analysis of costs and benefits - Luc Lens; Luc A. Wauters; Andr A. Dhondt (Behavioral Ecology and Sociobiology, 1994)

Nest-building by crested tit Parus cristatus males: an analysis of costs and benefits - L. Lens; Luc A. Wauters; Andr A. Dhondt (Behavioral Ecology and Sociobiology, 1994)

Individual variation in mate care by alpha males in crested tit winter flocks - Luc Lens; AndrA. Dhondt (Behavioral Ecology and Sociobiology, 1993)